Korelasi pola tidur dan kesepian dengan ide bunuh diri pada remaja - Chusnah, Aida Nurlaily; Widiyawati, Wiwik (Holistik Jurnal Kesehatan, 2025)
Background:  Suicide often occurs due to mental stress, sadness, or mental illness. Every year, more and more young people end their lives by committing suicide. This case is one of the highest causes of death among young people and young adults. Purpose: To determine the relationship between sleep patterns and loneliness with suicidal ideation in teenager. Method: Quantitative research with a cross-sectional design to analyze the relationship between sleep patterns and loneliness with suicidal ideation in adolescents. This study was conducted on November 8, 2024, on high school students in Gresik. The sample of this study was taken randomly and obtained 179 respondents. Data collection used instruments in the form of the Pittsburgh Sleep Quality Index (PSQI) questionnaire to determine sleep patterns, the UCLA questionnaire (version 3) to assess loneliness, and the small questionnaire +5.0 to determine suicidal ideation. The research data were analyzed using univariate and bivariate analysis of the Chi Square and Sperm rank tests. Results: Not all respondents had high category suicidal ideation, only most respondents had moderate category suicidal ideation as many as 131 (73.2%). Most respondents' sleep patterns were in the bad category as many as 111 (62.0%) with a p value of 0.91 (> 0.05), this shows that there is no significant influence between sleep patterns and suicidal ideation in adolescents. Most respondents felt low category loneliness as many as 97 (54.2%) with a p value of 0.00 and a correlation coefficient value of 0.04. This shows that there is a relationship between feelings of loneliness and suicidal ideation in adolescents. Conclusion: There is a relationship between loneliness and suicidal ideation, but no relationship was found between sleep patterns and suicidal ideation. Suggestion: Schools can provide counseling services that are more easily accessible to students, both individually and in groups. Teachers and school staff need to receive special training to recognize early signs of stress, depression, and other mental disorders in students, so that they can immediately provide the help needed.   Keywords: Loneliness; Suicidal Ideation; Sleep Pattern; Teenager.   Pendahuluan: Bunuh diri sering terjadi karena ketegangan mental, kesedihan, atau penyakit mental. Setiap tahun, semakin banyak anak muda yang mengakhiri hidupnya dengan bunuh diri. Kasus ini menjadi salah satu penyebab utama kematian di kalangan anak muda dan dewasa muda. Tujuan: Untuk mengetahui hubungan antara pola tidur dan kesepian dengan ide bunuh diri remaja. Metode: Penelitian kuantitatif menggunakan desain cross-sectional untuk menganalisis korelasi pola tidur dan kesepian dengan ide bunuh diri pada remaja. Penelitian ini dilakukan pada tanggal 8 november 2024 pada siswa di SMA di Gresik. Sampel penelitian ini diambil secara acak dan didapatkan sebanyak 179 responden. Pengumpulan data menggunakan instrumen berupa kuesioner Pittsburgh Sleep Quality Index (PSQI) untuk mengevaluasi pola tidur, kuesioner UCLA (versi 3) untuk menilai kesepian, dan kuesioner kecil +5.0 untuk mengevaluasi ide bunuh diri. Data hasil penelitian dianalisis menggunakan analisis univariate dan bivariate uji Chi Square dan Sperm rank. Hasil: Seluruh responden tidak memiliki ide bunuh diri kategori tinggi, hanya saja sebagian besar responden memiliki ide bunuh diri kategori sedang sebanyak 131 (73.2%). Pola tidur responden mayoritas dalam kategori buruk sebanyak 111 (62.0%) dengan perolehan p-value sebesar 0.91 (>0.05), hal ini menunjukkan bahwa tidak ada pengaruh signifikan antara pola tidur dengan ide bunuh diri pada remaja. Sebagian besar responden merasakan perasaan kesepian kategori rendah sebanyak 97 (54.2%) dengan perolehan p-value 0.00 dan nilai koefisien korelasi sebesar 0.04. Hal ini menunjukkan bahwa ada keterkaitan antara perasaan kesepian dengan ide bunuh diri pada remaja. Simpulan: Terdapat hubungan antara kesepian dengan ide bunuh diri, tetapi tidak ditemukan hubungan antara pola tidur dengan ide bunuh diri. Saran: Pihak sekolah dapat menyediakan layanan konseling yang lebih mudah diakses oleh siswa, baik secara individu maupun dalam kelompok. Guru dan staf sekolah perlu mendapatkan pelatihan khusus untuk mengenali tanda-tanda awal stres, depresi, dan gangguan mental lainnya pada siswa, sehingga dapat segera memberikan bantuan yang dibutuhkan.   Kata Kunci: Ide Bunuh Diri; Kesepian; Pola Tidur; Remaja.